Estimating apparent survival of songbirds crossing the Gulf of Mexico during autumn migration. Issue 1889 (24th October 2018) - Ward, Michael P.; Benson, Thomas J.; Deppe, Jill; Zenzal, Theodore J.; Diehl, Robert H.; Celis-Murillo, Antonio; Bolus, Rachel; Moore, Frank R.
Abstract : Many migratory bird species are declining, and the migratory period may limit populations because of the risk in traversing large geographical features during passage. Using automated radio-telemetry, we tracked 139 Swainson's thrushes ( Catharus ustulatus ) departing coastal Alabama, USA and crossing the Gulf of Mexico to arrive in the Yucatan Peninsula, Mexico during autumn. We estimated apparent survival and examined how extrinsic (weather variables and day of year) and intrinsic (fat load, sex and age) factors influenced survival using a mark-recapture approach. We also examined how favourability of winds for crossing the Gulf varied over the past 25 years. Fat load, day of year and wind profit were important factors in predicting which individuals survived crossing the Gulf. Survival estimates varied with wind profit and fat, but generally, fat birds departing on days with favourable wind profits had an apparent survival probability of greater than 0.90, while lean individuals with no or negative wind profits had less than 0.33. The proportion of favourable nights varied within and among years, but has increased over the last 25 years. While conservation strategies cannot improve extrinsic factors, they can provide opportunities for birds to refuel before crossing large geographical features through protecting and creating high-quality stopover sites.